URGENSI KEPRIBADIAN DALAM ORGANISASI BISNIS - Hamdani Taha (MUAMALAH, 2015)
Daily activities, will be found a wide variety of characteristics of employees. Some are aggressive, calm, explosiveness, ambitious, sociable, passive, and so forth. The characteristics of these employees is a categorization based on personality. So it can be defined as a combination of personality traits that describe a person's psychological. Organizational behavior is essentially the result of interaction between individuals within the organization.Organizational behavior basically focused on two scopes. First, review the behavior of individuals within the organization, such as attitude, personality, perception, learning and motivation. Secondly, the behavior of groups within the organization, which include norms, roles, team building and conflict. Therefore, coverage is so extensive organizational behavior, before understanding the behavior of the organization first needs to understand individuals as one dimension in the organization is very important and is one of the supporting factors in theorganization